Fortunatianus Aquileiensis Commentary on the Gospels English translation and introduction - Houghton, H.A.G (Corpus Scriptorum Ecclesiasticorum Latinorum [Extra Seriem], 2017)
The commentary as transmitted in the Cologne manuscript consists of four principal sections: an initial section on the characteristics of the four Gospels (praef., lines 1- 133 of the edition);20 an extensive exposition of Matthew 1:1-2:18, apparently in three chapters (M. long. I-III, lines 134-574); a numbered list of the titles for each of the 160 sections of the full commentary (cap. M. I-CXXVIIII / cap. L. I-XIII / cap. J. I-XVIII, lines 575-755); the commentary itself, treating almost all of the Gospel according to Matthew in 129 chapters (M. I-CXXVIIII) followed by a portion of Luke in 13 chapters (L. I-XIII) and the opening of John in 18 chapters (J. I-XVIII) (lines 756-3306). There is no initial dedicatory letter or statement of authorial intent. The indication of the end of a given section, explicit, is found at the end of the first two parts and also at the end of the whole commentary in the Cologne manuscript (lines 133, 574 and 3306). Nevertheless, the unity of the work is demonstrated by internal connections. In particular, the first seven chapters of the full commentary refer back to the earlier, more detailed treatment of the beginning of Matthew, which itself contains an indication of the commentary to follow and a reference to the preceding introduction.21 The critical edition by Dorfbauer includes, as an Appendix, two passages from the "Pseudo-Theophilus" commentary which may represent borrowings from Fortunatianus in sections missing from all extant witnesses to the commentary ("Excerpta dubia").